Exhaustive Swimming Exercise Related Kidney Injury in Rats – Protective Effects of Acetylbritannilactone - Wu, G. L.; Chen, Y. S.; Huang, X. D.; Zhang, L. X. (International Journal of Sports Medicine, 2012)
The aim of this study was to investigate the protective effects of acetylbritannilactone (ABL) on renal injury induced by acute exhaustive exercise in the rat. The exhaustive exercise induced kidney injury in rats was established by exhaustive swimming (ES). ABL (26 mg/kg) or polyglycol (control) were administrated orally by gastric gavage 24 h before training. Renal function, biochemical index, renal histopathological change, oxidative stress indices, renal cell apoptosis and inflammatory molecules were checked after ES, for 6 h and 24 h. It was found that immediately after exhaustive swimming, the serum urea and creatinine were significantly higher in ES rats, and the same for serum creatine kinase. All the values were reduced in the ES rats treated with ABL. The increase of superoxide dismutase activity and decrease of malondialdehyde content in the kidney were found in rats with ABL treatment. Tubular cell apoptosis at different time points after ES were significantly reduced by the ABL treatment. The increased expression of TNF-α and NF-κB induced by ES was also significantly decreased by ABL treatment. Our results suggest that ABL protects rats from overtraining-induced kidney injury by inhibiting renal cell apoptosis and suppressing oxidative-stress generation and inhibiting inflammation.
Keywords: acetylbritannilactone; acute kidney injury; exhaustive swimming